Identity digitalization as dispossession and entrenched displacement: digitalization at the nexus of migration “management” and climate change in Thailand and Türkiye - Flaim, Amanda; Nawyn, Stephanie J. (Frontiers in Human Dynamics, 2024)
Digitalizing technologies are increasingly heralded by a range of powerful actors and some human rights organizations as appropriate and necessary tools for 'managing migration' and mitigating climate change. Yet, just as exclusionary and marginalizing discourses of "migration problems" serve to justify the digital surveillance of vulnerable and precariously statused people, the context of climate change, accelerating contestation over land and water, and discourses of catastrophe prove fertile ground for entrenching these practices and technologies in multiple ways. Researchers are identifying the dispossessive power of digitalization in the arena of personal identification and in relation to resource and land mapping, yet these dynamics are rarely interrogated in connection. In this comparative analysis, we draw from sustained ethnographic engagement and insights in critical digitalization studies and political economy to analyze the consequences of state efforts to digitalize identity and resources in Thailand and Türkiye in the age of the Anthropocene. Our research points to a need for greater attention to the ways that state efforts to digitalize identification and registration of immigrant, refugee, and stateless people links with, and can facilitate, more efficient dispossessions and displacements of precariously statused communities from vital and contested lands.